The Prevalence of Speech and Language Disorders in Patients Referred to Speech Therapy Clinics of Hamadan University of Medical Sciences from 2013 to 2022 - Bahareh Rezaei; Ailin Talimkhani (پزشکی بالینی ابن سینا)
Background and Objective: Knowledge of the prevalence of speech and language disorders (SLDs) can help speech and language pathologists (SLPs) in planning effective rehabilitation interventions. The aim of this study was to investigate the prevalence of SLDs in patients referred to the speech therapy clinics of Hamadan University of Medical Sciences from 2013 to 2022. Materials and Methods: In this descriptive-analytical and cross-sectional study, 1,468 records from the archives of the speech therapy clinics of the School of Rehabilitation were examined by census. The desired data was collected through a questionnaire, and the extracted data was analyzed in SPSS 16 using central dispersion indices, including frequency distribution and frequency percentage. The Chi-Square test was used to calculate the prevalence of SLDs according to age and gender. The significance level was considered less than 0.05. Results: According to the findings, 51.3% of clients were 3 to 6 years old. The prevalence of speech sound production disorder was 18.9%, delay in speech and language was 18.1%, was stuttering 18%, voice disorder was 12.1%, developmental language disorders was 9.2%, swallowing disorder was 2.5%, aphasia was 2%, dysarthria was 1.7%, dyslexia was 1%, and apraxia of speech was 0.3%. The results of Chi-square test also showed that there was a significant difference in the frequency of speech and language disorders between both genders and age groups (P=0.001). Conclusion: Given the higher prevalence rate of SLDs in children aged 3 to 6 years, it is necessary to perform the screening of speech disorders in preschool children by SLPs more seriously.